Non-HLA Antibodies Impact on C4d Staining, Stellate Cell Activation and Fibrosis in Liver Allografts. Issue 10 (October 2017) - O'Leary, Jacqueline G.; Demetris, Anthony J.; Philippe, Aurélie; Freeman, Robert; Cai, Junchao; Heidecke, Harald; Smith, Cory; Hart, Brent; Jennings, Linda W.; Catar, Rusan; Everly, Mathew; Klintmalm, Goran B.; et al.
Abstract : Background: Recent data have shown an increased risk for rejection, fibrosis progression, and death in liver transplantation (LT) recipients with preformed or de novo HLA donor-specific alloantibodies (DSA). However, the role of non-HLA autoantibodies and the interaction between HLA DSA and non-HLA autoantibodies remains uncharacterized. Methods: We analyzed 1269 primary LT recipients from 1 of 2000 to 4 of 2009 with known HLA DSA status for angiotensin II type-1 receptor and endothelin-1 type A receptor autoantibodies pre-LT, and year 1 post-LT. Results: Preformed non-HLA autoantibodies alone did not impact outcomes. In multivariable modeling, the combination of preformed non-HLA autoantibodies and HLA-DSA were associated with an increased risk for death (hazard ratio [HR], 1.66; P = 0.02) especially if the HLA DSA was of the IgG3 subclass (HR, 2.28; P = 0.01). A single de novo non-HLA autoantibody was associated with an increased risk for T cell–mediated rejection or antibody-mediated rejection (68% vs 41%, P = 0.01) and fibrosis progression (HR, 1.84; P = 0.02). Biopsies with de novo non-HLA autoantibodies revealed a new sinusoidal C4d staining pattern when compared with HLA DSA (71% vs 3%; P < 0.001). Liver sinusoidal endothelial cell activation and stellate cell activation was increased in patients with non-HLA autoantibodies in the location of C4d positivity. Conclusions: A non-HLA autoantibody combined with a preformed HLA DSA is associated with an increased mortality risk. Isolated de novo anti-angiotensin II type-1 receptor and anti-endothelin-1 type A receptor autoantibodies are associated with an increased risk of rejection and fibrosis progression. The novel location of C4d staining in proximity to liver sinusoidal endothelial cell capillarization and stellate cell activation demonstrates allograft injury in proximity to non-HLA autoantibody binding. Abstract : The authors of this large study explore the new potential implications of non-HLA autoantibodies in liver transplant recipients, highlighting a novel location of C4d staining. Supplemental digital content is available in the text.